2008
DOI: 10.1007/s00256-008-0446-3
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow edema pattern in advanced hip osteoarthritis: quantitative assessment with magnetic resonance imaging and correlation with clinical examination, radiographic findings, and histopathology

Abstract: The amount of BME in the OA hip, as measured by MRI, correlates with the severity of pain, radiographic findings, and number of microfractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
155
2
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(166 citation statements)
references
References 25 publications
4
155
2
5
Order By: Relevance
“…The focal chondral defects noted in our patients, especially those whose lesions were associated with cystic subchondral changes, are similar to global clinical pathologic and radiologic findings associated with end-stage arthrosis [20]. Nevertheless, the mean Tegner-Lysholm score at 29-month followup was 7.4, representing the capacity to participate in competitive-level athletics.…”
Section: Discussionmentioning
confidence: 65%
“…The focal chondral defects noted in our patients, especially those whose lesions were associated with cystic subchondral changes, are similar to global clinical pathologic and radiologic findings associated with end-stage arthrosis [20]. Nevertheless, the mean Tegner-Lysholm score at 29-month followup was 7.4, representing the capacity to participate in competitive-level athletics.…”
Section: Discussionmentioning
confidence: 65%
“…9 These findings can be seen in patients with osteoarthritis of the hip. 10 In the present study, 7 (47%) of 15 hips showed the BME lesions in both the femoral head and acetabulum. In contrast, no cases showed a low-intensity band (fracture line) on MR images in both the femoral head and acetabulum.…”
Section: Discussionmentioning
confidence: 84%
“…A few publications have demonstrated clearly that this was not the case and that BMLs are histologically much more complex with fibrosis, cellular infiltration, and bony damage including micro fracturing. Edema was not a significant feature [13,14]. That is not to say that bone marrow edema does not occur in other conditions, such as acute trauma, but in OA the pathology is different.…”
Section: So Where Does the Problem Lie?mentioning
confidence: 95%